Social inequalities among Brazilian older adults: a secondary cross-sectional analysis of a national survey - Eloah Costa de Sant Anna Ribeiro; Michele Ribeiro Sgambato; Paulo Cesar Pereira de Castro Junior; Karina Cardoso Meira; Rosana Salles-Costa; Aline Alves Ferreira (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: This study aimed to evaluate sociodemographic and economic differences among Brazilian older adults according the region they live in. Methods: This cross-sectional, descriptive-analytical study included older adults aged ≥ 60 years, based on a secondary analysis of public data from a nationally representative survey called the Family Budget Survey. The data were disaggregated according to the 5 regions of the country and associated with sociodemographic and economic characteristics. Analyses of categorical and numerical variables and their associations were performed using multinomial logistic regression. Results: Among all participants in the Family Budget Survey, 26 199 (15%) were older adults. The southeast and south regions were found to had better living conditions and higher proportions of older adults. Regarding race, the southern region had the highest proportion of self-declared Whites, the southeastern region had the highest mean education level, and the northern and northeastern regions had the lowest levels of education and household income. Conclusions: The results suggest that the aging process is heterogeneous due to marked regional inequalities, which are related to social issues. Regional differences can be determinant in socioeconomic and demographic inequalities among the older population.